2021
DOI: 10.1093/hmg/ddab207
|View full text |Cite
|
Sign up to set email alerts
|

Effective therapeutic strategies in a preclinical mouse model of Charcot–Marie–Tooth disease

Abstract: Charcot–Marie-Tooth (CMT) disease is a neuropathy that lacks effective therapy. CMT patients show degeneration of peripheral nerves, leading to muscle weakness and loss of proprioception. Loss of mitochondrial oxidative phosphorylation proteins and enzymes of the antioxidant response accompany degeneration of nerves in skin biopsies of CMT patients. Herein, we followed a drug-repurposing approach to find drugs in an FDA-approved library that could prevent development of CMT disease in the Gdap1-null mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The mitochondrion is currently considered a therapeutic target that, in recent years, has caused great interest among the scientific and health communities. It has already been addressed in different pathologies, such as Charcot–Marie–Tooth disease, demonstrating that the avoidance of overproduction of ROS in the mitochondria with florfenicol as well as the prevention of oxidative damage with the antioxidant MitoQ prevent the progression of motor symptoms associated with this pathology as well as other cognitive and sensory symptoms [ 142 ]. This procedure is also being used in the treatment of alcoholic liver disease, which is responsible for up to 80% of liver-associated deaths and includes different pathological entities such as liver fibrosis, cirrhosis, simple steatosis, or hepatocellular carcinoma.…”
Section: Mitochondrial Dna Mutations In Brain Diseasementioning
confidence: 99%
“…The mitochondrion is currently considered a therapeutic target that, in recent years, has caused great interest among the scientific and health communities. It has already been addressed in different pathologies, such as Charcot–Marie–Tooth disease, demonstrating that the avoidance of overproduction of ROS in the mitochondria with florfenicol as well as the prevention of oxidative damage with the antioxidant MitoQ prevent the progression of motor symptoms associated with this pathology as well as other cognitive and sensory symptoms [ 142 ]. This procedure is also being used in the treatment of alcoholic liver disease, which is responsible for up to 80% of liver-associated deaths and includes different pathological entities such as liver fibrosis, cirrhosis, simple steatosis, or hepatocellular carcinoma.…”
Section: Mitochondrial Dna Mutations In Brain Diseasementioning
confidence: 99%
“…Recently, high-dose PXT3003 (baclofen/naltrexone/D-sorbitol) has demonstrated significant therapeutic effects in patients with CMT1A and has emerged as a promising treatment option [46] . HDAC6 inhibitors have shown positive effects on axonal defects in mouse models of several forms of CMT [47][48][49] , opening a new window in the pharmacological treatment of CMT disease [50,51] . Antioxidant therapy with either the veterinary antibiotic florfenicol or mitoQ has also shown effectiveness in a knockout model of GDAP1-related CMT when starting administration very early in mouse life, but not in older mice [52] .…”
Section: Treatmentmentioning
confidence: 99%
“…Particularly promising examples of such repurposed agents in the realm of NM disease management include the free radical scavenger edaravone for amyotrophic lateral sclerosis ( Aoki et al, 2011 ; Takei et al, 2017 ; Shah et al, 2021 ), metformin for Steinert myotonic dystrophy (DM1) ( Bassez et al, 2018 ; Gutiérrez-Gutiérrez and Rosado-Bartolomé, 2020 ), and omaveloxolone and deferiprone for Friedreich’s ataxia ( Lynch et al, 2021 ; Shah, Dooms, Amaral-Garcia and Igoillo-Esteve, 2021 ), all of which have demonstrated some clinical improvement in individuals or patient cohorts. Additionally, several recent reports have indicated enhanced potential of selected repurposed therapies in animal or tissue-derived cellular models for significant neuromuscular disorders, for example metformin in BAG3 myofibrillar myopathy models ( Ruparelia et al, 2021 ), moxifloxacin ( Januel et al, 2022 ) and VPA + PMO combination therapy (and other varied PMO-combination modalities) for SMA ( Farrelly-Rosch et al, 2017 ; Richelme, 2019 ), and the antibiotic florfenicol for Charcot-Marie-Tooth (CMT) disease ( Nuevo-Tapioles et al, 2021 ). Although several classes and instances of repurposed drugs have been examined for potential against DMD, including metformin, tamoxifen, simvastatin, gentamicin, and tadalafil ( Vitiello et al, 2019 ), most are in pre-clinical stages or have not demonstrated significant clinical improvement.…”
Section: Introductionmentioning
confidence: 99%